Direct modulation of TRPM4 and TRPM3 channels by the phospholipase C inhibitor U73122. (18th July 2016) - Leitner, Michael G; Michel, Niklas; Behrendt, Marc; Dierich, Marlen; Dembla, Sandeep; Wilke, Bettina U; Konrad, Maik; Lindner, Moritz; Oberwinkler, Johannes; Oliver, Dominik
Abstract : Background and Purpose: Signalling through phospholipase C (PLC) controls many cellular processes. Much information on the relevance of this important pathway has been derived from pharmacological inhibition of the enzymatic activity of PLC. We found that the most frequently employed PLC inhibitor, U73122, activates endogenous ionic currents in widely used cell lines. Given the extensive use of U73122 in research, we set out to identify these U73122‐sensitive ion channels. Experimental Approach: We performed detailed biophysical analysis of the U73122‐induced currents in frequently used cell lines. Key Results: At concentrations required to inhibit PLC, U73122 modulated the activity of transient receptor potential melastatin (TRPM) channels through covalent modification. U73122 was shown to be a potent agonist of ubiquitously expressed TRPM4 channels and activated endogenous TRPM4 channels in CHO cells independently of PLC and of the downstream second messengers PI(4, 5)P2 and Ca 2+ . U73122 also potentiated Ca 2 + ‐dependent TRPM4 currents in human Jurkat T‐cells, endogenous TRPM4 in HEK293T cells and recombinant human TRPM4. In contrast to TRPM4, TRPM3 channels were inhibited whereas the closely related TRPM5 channels were insensitive to U73122, showing that U73122 exhibits high specificity within the TRPM channel family. Conclusions and Implications: Given the widespread expression of TRPM4 and TRPM3 channels, these actions of U73122 must be considered when interpreting its effects on cell function. U73122 may also be useful for identifying and characterizing TRPM channels in native tissue, thus facilitating the analysis of their physiology.